Prognostic significance of tumor regression grade in esophageal squamous cell carcinoma after neoadjuvant chemoradiation - Zhang, Chi; Xu, Fei; Qiang, Yong; Cong, Zhuang-Zhuang; Wang, Qin; Zhang, Zheng; Luo, Chao; Qiu, Bing-Mei; Hu, Li-Wen; Shen, Yi (Frontiers in Surgery, 2023)
Backgrounds: Trimodal therapy (neoadjuvant chemoradiotherapy followed by esophagectomy) for locally advanced esophageal squamous cell carcinoma (ESCC) is associated with a significant survival benefit. Modified Ryan score is an effective tool to evaluated the tumor regression grade (TRG) after neoadjuvant therapy. The aim of this study was to evaluate the prognostic value of TRG for overall survival (OS) and disease-free survival (DFS) in ESCC patients undergoing neoadjuvant chemoradiation. Methods: The study retrospectively reviewed 523 ESCC patients who underwent neoadjuvant chemoradiotherapy and radical esophagectomy at Jinling Hospital from January 2014 to July 2020. Kaplan–Meier curves with log-rank test and Cox regression model were used to evaluate the prognostic factor of TRG based on modified Ryan scoring system on OS and DFS. Results: After application of inclusion and exclusion criteria, 494 patients with ESCC following neoadjuvant chemoradiotherapy and radical esophagectomy were available for analysis. The TRG scores are significantly associated with smoke history (p = 0.02), lymphovascular invasion (LVI) and/or peripheral nerve invasion (PNI) (p < 0.01), and postoperative adjuvant therapy (p < 0.01). Meanwhile, tumor characteristics including tumor length (p < 0.01) and tumor differentiation grade (p < 0.01) are also significantly associated with TRG score. The results of multivariable Cox regression modal showed that TRG is not an independently prognostic factor for OS (p = 0.922) or DFS (p = 0.526) but tumor length is an independently prognostic factor for DFS (p = 0.046). Conclusions: This study evaluated the prognostic value of modified Ryan scoring system for ESCC after trimodal therapy and concluded that modified Ryan scoring system can predict survival and recurrence rates but is not an independently prognostic factor for OS and DFS.